Factors causing peak energy consumption of reefers at container terminals - J. H. R. van Duin; H. Geerlings; Lorant A. Tavasszy; D. L. Bank (Journal of Shipping and Trade (JST), 2019)
Reefers are refrigerated containers commonly used for transporting perishable goods such as meat, fish, vegetables and fruit. Nowadays, reefers are responsible for 40% of the total energy consumption of container terminals, when connected to the electricity grid on shore. Every time when a large number of reefers is plugged-in after arrival, peaks in energy consumption occur. As container terminals purchase energy using a demand-based fee, exceeding the reserved capacity during peak times increases the energy costs of the terminal significantly. So far the literature has not dealt with the root causes of peak energy consumption of reefers, or ways to reduce these peaks. The aim of this paper is to identify the root causes and to quantify their importance. We use data of energy consumption of reefers at a large container terminal, over the period of 1 year. In order to identify the importance of factors, we apply a sequential multiple regression analysis approach with backwards feature selection. Variations in energy demand are explained for 77% by the arrival pattern of containers, for about 5% by dwell time and for 2% by other factors, such as container temperature at plug-in. Promising approaches to reduce peak energy consumption of reefers includes dynamic pricing, energy management and specific peak shaving strategies.
Keywords: 650; Reefers; Energy consumption; Container terminals; Data analysis; Regression analysis